Isolation and characterization of novel lytic bacteriophages against (fluoro)quinolone-resistant Campylobacter strains - Calancha-Padrón, Yuran Elías; Perez-Condori, Dayana; Gutierrez-Valverde, Marcelo Fernando; Salas-Veizaga, Daniel Martin; Hjort, Karin; Alvarez-Aliaga, María Teresa (Frontiers in Microbiology, 2026)
Antimicrobial resistance (AMR) has become a global public health concern, particularly in developing countries where antibiotics are often overused and misused. In Bolivia, the indiscriminate use of antibiotics, including (fluoro-)quinolones, has led to the proliferation of multidrug-resistant (MDR) Campylobacter spp., increasing the risk of resistance gene dissemination to other bacteria, and further deepening the AMR problem. To help mitigate the proliferation of MDR bacteria, bacteriophages can be a valuable complementary treatment to antibiotics. In the present study, we isolated and characterized three novel lytic bacteriophages with activity against (fluoro-)quinolone-resistant Campylobacter isolates and C. jejuni strains. The isolated bacteriophages, BMBo_CjP_006, BMBo_CjP_007, and BMBo_CjP_009, belong to the class Caudoviricetes and possess a linear double-stranded DNA genome. Their genome size ranges from 59 to 77 kb, with a GC-content between 42 to 46%. The 90, 144, and 146 predicted coding sequences (CDSs) of the different bacteriophages did not encode any antibiotic resistance, virulence, or lysogenic-associated genes, confirming their genetic safety and lytic nature. The isolated bacteriophages showed a narrow host range and lytic activity against nine (fluoro-)quinolone-resistant Campylobacter spp., including C. jejuni, with lytic activity varying at MOIs from 0.1 to 100, dependent on bacteriophage and host isolate. In addition, the bacteriophages were stable across a pH range of 4 to 10 and a temperature range of −20 °C to 70 °C. These characteristics make them promising for biotechnological applications due to their lytic activity, lack of resistance and virulence genes, and potential utility for product preservation.